Pendampingan Belajar Siswa Speech Delay di RA Hidayatus Shibyan Senori Tuban - Eka Nurul Fitrianingsih; Nur Lailatul Fitri; Nurul Novitasari (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to find out the form of learning assistance for speech delay students at RA Hidayatus Shibyan and find out the obstacles experienced by teachers when teaching speech delay students. Language development is very important for every child because language aims to facilitate communication and express the feelings of early childhood. The research method used was descriptive qualitative, with the research subject being a student who experienced speech delay, 1 class teacher, and 1 accompanying teacher. Data collection techniques through observation, interviews, and documentation. The results of this study are 1) learning assistance for children who experience speech delay is carried out using a floor time approach and through learning methods, 2) while the obstacles experienced by teachers are that students often make mistakes or forget the pronunciation they have learned before, and lack of support and stimulation provided by parents at home